“Tinder Humanitarians”: The Moral Panic Around Representations of Old Relationships in New Media - Richey, Lisa Ann (Javnost-The Public, 2016)
According to the company website, Tinder is a mobile phone application for “friends, dates, relationships, and everything in between”. Cody Clarke, a writer and filmmaker, documents screenshots of photographs from the closed network of Tinder to publicly “out” users of the site who post photographs showing themselves in some “do-gooding” relationship that appears to take place in the South. Through the posting of a new photograph every day, the “Humanitarians of Tinder” Tumblr blog and Facebook page have generated a public discussion on the politics of representing suffering strangers in attempts to enhance the appeal of western image producers. This article will investigate the phenomenon of the Humanitarians of Tinder in order to understand its representations of North–South relations from the photographs themselves and from the debates held around them in new media and old. Critical development studies, media studies and sociology will provide an interdisciplinary theoretical framework to understand the moral panic that these Tinder humanitarians have created through posting private photographs of humanitarian performances to increase their personal desirability.